Republic of Azerbaijan : Staff Report for the 2014 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2014)
This 2014 Article IV Consultation highlights that recent economic developments in Azerbaijan have been favorable. In 2013, a stabilization of oil output and strong non-oil growth at nearly 10 percent helped lift overall GDP growth to 5.8 percent. Inflation remained low, averaging 2.4 percent, restrained by soft food prices and a stable exchange rate. The impact of regional market turbulence in early 2014 has been limited, with few signs of lower manat demand or capital flight. Economic prospects over the near and medium term are positive, if underpinned by fiscal consolidation and supported by reforms to spur non-oil private sector activity.